Diálogos entre o corpo e o traje: costuras dos processos criativos do figurino e da dança no Coco de Roda do Ipiranga do município de Conde na Paraíba - Gomes, Isabel Cristina de Lima (2024)
In this research - ‘DIALOGUES BETWEEN THE BODY AND THE COSTUME: seams of the creative processes of costume and dance in the Coco de Roda of Ipiranga in the Municipality of Conde in Paraíba’ - I aim at the development of a teaching-learning work from an anti-racist and decolonial perspective directed to the study of Afro-Brazilian culture, based on dance and costume as elements of black resistance. We conducted the study of the cultural manifestation Coco de Roda Novo Quilombo do Ipiranga in an intercultural dialogue with the work Parangolés, by the plastic artist Hélio Oiticica. In this study, the aim is to stimulate the reflection of the popular costume as a symbol of struggle and cultural resistance. And for specific objectives to promote an intercultural dialogue in the sense of valuing the black quilombola cultural identity of the Municipality of Conde; to propose teaching practices to combat racial prejudices in school, to make capes/parangolés, to dress them and to present the choreography Coco Parangolé. The study was developed between August and December 2022, with 8th grade students, and was then resumed from May to June 2023, with the students who remained and who went on to study in the 9th grade of the Municipal School of Basic Education and EJA Professora Noêmia Alves de Souza, located in the Municipality of Conde, in Paraíba. The theoretical-practical study is aimed at visual and scenic artistic languages, carried out in 3 stages: first in the knowledge of the culture of Coco de Roda and Parangolés, in the field class in Quilombo do Ipiranga and in the making of costumes (Parangolés); second in the experience of wearing the created Parangolés, producing the choreography and rehearsing. And finally, the presentation of the performance Coco Parangolé. The choreography was produced with references to the culture of Coco de Roda, Capoeira and Ciranda, in addition to improvised movements. This is an action research of a qualitative nature in which were used for data analysis: field diary, filming, photographs, interviews, conversation circles and productions of the students that contributed to the realization of this research. The results obtained contributed to the understanding of the importance of the knowledge of black culture to understand the process of formation of the quilombola people, having in Coco de Roda the symbol of resistance and struggle for lands in Paraíba. Therefore, we believe it is important to think about a teaching learning process that stimulates the knowledge of our cultural diversity for debate on racial issues in education in Brazil.